Nix the BRICs—At Least for the Higher Education Debate - Altbach, Philip G; Bassett, Roberta Malee (International Higher Education, 2014)
Comparing the BRIC countries—Brazil, Russia, India, and China—in terms of higher education does not make good sense. The only thing in common is that they are large academic systems. However, they quite different in terms of history, economic realities, patterns of coordination and governance, and other factors. This article argues that it is not useful to place the BRIC countries in any kind of common framework for comparison.